Balancing Disaster Risk Perception and Natural Tourist Attractions in Tebing Keraton: Menyeimbangkan Persepsi Risiko Bencana dan Daya Tarik Wisata Alam Tebing Keraton - Sahid Han Hidayatulloh; Yosef Abdul Ghani (Academia Open, 2026)
General Background Indonesia possesses immense natural tourism potential but sits within the highly active Ring of Fire, necessitating sustainable and safe destination management. Specific Background Tebing Keraton in northern Bandung has rapidly developed as a prime nature destination despite its proximity to the active Lembang Fault and landslide-prone topography. Knowledge Gap Previous literature predominantly discusses destination development or macro-level policies, leaving a deficit in understanding how stakeholders specifically negotiate the intersection of aesthetic appeal and geological threats. Aims This qualitative case study explores how tourists, local communities, and destination managers perceive and respond to disaster risks while maintaining the area's natural appeal. Results Through interviews and observations, findings indicate that tourists prioritize panoramic views, such as sunrises and cloud seas, perceiving geological risks as reasons for caution rather than deterrents. Destination managers and locals collaboratively implement structural and non-structural safety measures, including warning boards, safety fences, and evacuation routes, without compromising the site's natural beauty. Novelty This research distinctly captures the synergistic relationship between aesthetic tourist motivations and multi-stakeholder risk mitigation practices within a specific active fault zone. Implications Destination developers must continuously integrate proactive safety infrastructure and educational risk communication to guarantee sustainable nature-based tourism in geographically vulnerable regions. Highlights Tourists prioritize panoramic landscapes over geological threats, treating disaster awareness as a precautionary measure rather than a visitation deterrent. Destination managers and local communities collaboratively implement safety fences and evacuation routes without compromising the natural aesthetic appeal. Proactive risk communication and structural mitigation are essential for maintaining sustainable nature-based tourism in active fault zones. Keywords Disaster Risk Perception; Natural Tourist Attractions; Tebing Keraton Destination; Geological Risk Mitigation; Sustainable Tourism Management